Experience and self-consciousness - Schear, J (2009)
Does all conscious experience essentially involve self-consciousness? In his Subjectivity and Selfhood: Investigating the First-Person, Dan Zahavi answers "yes". I criticize three core arguments offered in support of this answer-a well-known regress argument, what I call the "interview argument," and a phenomenological argument. Drawing on Sartre, I introduce a phenomenological contrast between plain experience and self-conscious experience. The contrast challenges the thesis that conscious experience entails self-consciousness. © 2009 Springer Science+Business Media B.V.